Synthesis and characterization of tetra-armed-thiosemicarbazone and its salen/salophen capped transition metal complexes: Investigation of their thermal and magnetic properties. Issue 22 (16th November 2016) - Uysal, Şaban; Er, Mustafa; Tahtaci, Hakan
ABSTRACT: In this work, we aimed to synthesize and characterize a novel tetra-directional ligand, (2 E, 2′ E )-2, 2′-((((2-(1, 3-bis(4-(( E )-(2-carbamothioylhydrazono)methyl)phenoxy)propan-2-ylidene)propane-1, 3-diyl)bis(oxy))bis(4, 1-phenylene))bis(methanylylidene))bis(hydrazinecarbothioamide)(5), including thiosemicarbazone group and its novel tetra-directional-tetra-nuclear Schiff base complexes. For this purpose, we used 1, 4-dibromo-2, 3-bis(bromomethyl)but-2-ene(2) as starting material. 4, 4′-((2-(1, 3-Bis(4-formylphenoxy)propan-2-ylidene)propane-1, 3-diyl) bis(oxy))dibenzaldehyde(3) was synthesized by the reaction of an equivalent 1, 4-dibromo-2, 3-bis(bromomethyl)but-2-ene(2) and 4 equivalents of 4-hydroxybenzaldehyde. Then, compound5 was synthesized in high yield (86%) by a condensation reaction of compound3 with thiosemicarbazide(4) . Finally, four novel tetra-nuclear Cr(III) or Fe(III) complexes of compound5 were synthesized. The synthesized compounds were characterized using elemental analyses, 1 H NMR, Fourier transform–infrared spectrometry, liquid chromatography–mass spectrometry (ESI + ), and thermal analyses. The metal ratios of the prepared complexes were determined using an atomic absorption spectrophotometer. We also investigated their effects on the magnetic behaviors of [salen, salophen, Cr(III)/Fe(III)] capped complexes. The complexes were found to be low-spin distorted octahedral Fe(III) and distorted octahedral Cr(III), all bridged by thiosemicarbazone. GRAPHICAL ABSTRACT: